Addressing the needs of older adults receiving alcohol treatment during the COVID-19 pandemic: a qualitative study. (27th April 2022) - Seddon, Jennifer; Trevena, Paulina; Wadd, Sarah; Elliott, Lawrie; Dutton, Maureen; McCann, Michelle; Willmott, Sarah
Abstract: Objectives: The COVID-19 global pandemic resulted in major changes to the provision of alcohol treatment in the UK, these changes coincided with increases in the use of alcohol. This study sought to understand the impact of the pandemic on older adults in alcohol treatment, and to explore how changes in the provision of alcohol treatment were experienced. Method: Semi-structured interviews were completed with older adults (aged 55+) in alcohol treatment, as well as alcohol practitioners providing support to older adults. Data were analysed using thematic analysis. Alcohol use was assessed using the Alcohol Use Disorders Identification Test – Consumption (AUDIT-C). Results: Thirty older adults in alcohol treatment and fifteen alcohol practitioners were recruited. The COVID-19 pandemic was found to result in both increases and decreases in alcohol use; changes in alcohol use depended on a number of factors, such as living arrangements, family support, physical and mental health. Many alcohol treatment services moved to a model of remote support during the pandemic. However, face-to-face service provision was considered to be essential by both older adults in alcohol treatment and alcohol practitioners. Engagement with online support was low, with older adults facing barriers in using online technology. Conclusion: The study highlights the importance of face-to-face treatment and intervention for older adults in alcohol treatment. Addiction services may see increased demand for treatment as a result of the pandemic; it is important that services consider the needs of older adults, many of whom may be marginalised by a remote model of service provision.